An ozone oxidation catalyst based on electrolytic anode manganese slag and preparation method thereof
Through the preparation method of ozone oxidation catalyst based on electrolytic anode manganese slag, the problem of treatment of lead impurities and organic pollutants in electrolytic anode manganese slag is solved, the optimization utilization of manganese resources and the recovery of lead are realized, and the efficiency and stability of the catalyst are improved. Organic wastewater treatment suitable for the new energy industry.
Patent Information
- Application Number
- CN202410124612.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-01-30
- Publication Date
- 2024-12-17
- Estimated Expiration
- 2044-01-30
AI Technical Summary
The prior art is difficult to effectively deal with lead impurities and organic pollutants in the electrolytic anode manganese slag, and the resource utilization is insufficient, resulting in environmental pollution and waste of resources.
The preparation method of ozone oxidation catalyst based on electrolytic anode manganese slag is adopted. By mechanical activation and mixing iron salt solution, the iron content is increased to enhance the catalytic effect, and the recovery of lead and the magnetic enhancement of the catalyst is achieved through the granulation and roasting of the binder. .
It realizes the optimal allocation of manganese resources and the recovery of lead, reduces the cost of catalysts, improves the efficiency and stability of catalysts, and can efficiently degrade organic wastewater in the new energy industry, especially bis(2-ethylhexyl)phosphate. The COD removal rate reached 83%.
Smart Images

Figure CN118079950B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of catalysts, and in particular relates to a method for preparing an ozone oxidation catalyst based on electrolytic anode manganese slag. Background Art
[0002] Metallic manganese is widely used in nonferrous metallurgy, steel industry, chemical industry, battery, agriculture and other fields. my country's high-quality manganese metal is mainly prepared by electrolysis of manganese sulfate solution. During electrolysis, metallic manganese and trace amounts of other metal ions are deposited at the cathode and mixed in the manganese flakes. Hydrogen and manganese dioxide deposits are precipitated at the anode, which is the anode slag. In industrial production, multi-element alloys such as lead, antimony, tin, and silver are generally used as anode materials. Therefore, the anode slag contains a certain amount of lead, and the hydrated oxides of manganese and lead are closely symbiotic. Most manganese oxides are colloidal and colloidal ring-band structures, and the crystal form is not well developed. It is difficult to purify manganese by mechanical sorting. It is a highly toxic hazardous waste. If it is not handled properly, it will not only cause a serious waste of manganese resources, but also cause serious pollution to the environment.
[0003] At present, there are mainly two aspects about manganese anode slag, namely harmless treatment and comprehensive utilization of resources. Patent CN112760487A discloses a method for recovering manganese and lead from electrolytic manganese anode slag. The method utilizes hydrogen obtained by ammonia decomposition to evaporate the lead in manganese slag into gas recovery, and the manganese slag reacts with dilute sulfuric acid to generate manganese sulfate solution, and then oxidizes to remove iron. This method requires the preparation of hydrogen reduction and then adds an oxidant to remove iron, and the processing cost is relatively high. Patent CN115261631A utilizes calcium hydride, hydrazine compounds, dilute sulfuric acid and electrolytic manganese anode slag to mix for reduction reaction, and the obtained leachate is added with an oxidant to remove impurities and then a vulcanizing agent is added to precipitate heavy metal ions. The reaction process is too long, which is not conducive to large-scale promotion in industry. At the same time, with the rapid development of my country's new energy battery field, the wastewater of producing new energy vehicle batteries, the large processing capacity demand of the main organic pollutant di(2-ethylhexyl) phosphate, and the high processing difficulty are all technical problems to be solved. Therefore, it is of great significance to study an effective, convenient, environmentally friendly and resource-based treatment method for electrolytic anode manganese slag, which can be directly used for the degradation of organic pollutants.
[0004] In view of the shortcomings of the prior art, the present invention develops a method for preparing an ozone oxidation catalyst based on electrolytic anode manganese slag, utilizing the characteristics of high manganese content and catalytic transition metals in electrolytic anode slag. The method can not only effectively recover lead impurities in the anode slag during the preparation, thereby achieving optimal allocation and sustainable development of manganese resources, but also alleviate the pressure of high prices of ozone catalytic oxidants and great difficulty in treating organic wastewater. Summary of the invention
[0005] In view of the shortcomings of the prior art, the first aspect of the present invention provides a method for preparing an ozone oxidation catalyst based on electrolytic anode manganese slag, aiming to effectively recover the lead impurities in the anode slag and realize the resource utilization of manganese. The electrolytic anode manganese slag has a manganese content of more than 50%, and other minor components include metal oxides of Pb, Al, Ca, Mg and Fe. The preparation method comprises the following steps:
[0006] (1) cleaning, mechanically activating and drying the electrolytic anode slag to obtain pretreated anode slag;
[0007] (2) mixing the pretreated anode slag obtained in step (1) with an iron salt solution, adjusting the pH value, filtering, drying, and grinding to obtain an iron-supplemented anode slag;
[0008] (3) preparing a binder solution;
[0009] (4) adding the iron-supplemented anode slag obtained in step (2) to the binder solution in step (3), stirring and granulating to obtain a prefabricated catalyst;
[0010] (5) Drying, calcining and cooling the prefabricated catalyst to obtain the ozone oxidation catalyst.
[0011] Preferably, in step (1), the mechanical activation is grinding activation, and the electrolytic anode slag is ground to a particle size of 10-75 um; and the drying temperature is 80°C-150°C.
[0012] Among them, the role of mechanical activation is to increase the fineness of the anode slag, change the bond energy of the mineral crystals, and promote the release of manganese by increasing the specific surface area of the anode slag.
[0013] Preferably, in the iron salt solution of step (2), the solvent is water, preferably a ferrous salt solution. Based on the molar amount of Mn in the anode slag, the molar ratio of Fe:Mn is 1:(1-10).
[0014] The inventors found that if the Fe:Mn molar ratio is lower than 1:1, the iron content is low, which is not conducive to the formation of a stable composite metal oxide after calcination; if it exceeds 1:10, excess iron will be generated, increasing the cost and process of subsequent removal.
[0015] Preferably, the pH value in step (2) is in the range of 8.5-9.5, and the pH value can be adjusted with sodium hydroxide.
[0016] Preferably, a dry powder grinder is used for grinding in step (2), and the drying temperature is 80°C-150°C.
[0017] The invention improves the fineness of anode slag through mechanical activation technology, changes the bond energy of mineral crystals, promotes the release of manganese elements by increasing the specific surface area of anode slag, and then increases the Fe concentration in anode slag to enhance the synergistic catalytic effect of iron and manganese.
[0018] Preferably, the ferrous salt is a mixed solution of an organic ferrous salt and an inorganic ferrous salt, and the organic ferrous salt solution is selected from ferrous lactate or ferrous gluconate solution; wherein the molar ratio of the organic ferrous salt to the inorganic ferrous salt is (1-2):10.
[0019] Preferably, the mass concentration of the ferrous salt solution is 5-20wt%.
[0020] The inventors have found that an iron salt system containing a small amount of organic ferrous salt is beneficial to the generation of gases such as carbon dioxide during the subsequent high-temperature roasting process, enriching the pore structure, thereby further improving the adsorption performance of the catalyst.
[0021] Preferably, the binder in step (3) is starch. Specifically, the starch is dissolved in deionized water, stirred and heated to 70-85° C. to obtain a uniform paste-like binder solution.
[0022] Preferably, the mass ratio of the binder in step (3) to the iron-replenishing anode slag obtained in step (2) is (1-3):1, and the granulation method is to first fully mix the iron-replenishing anode slag and the binder solution, and then feed them into a granulator to achieve granulation.
[0023] The present invention adds a binder to granulate the iron-filled anode slag by utilizing viscosity: by controlling the size, shape, and pore structure of the particles, the stability of the catalyst is preferably improved, more catalytic active sites are exposed, more hydroxyl radicals OH are decomposed, and the catalytic performance of the catalyst is improved; on the other hand, during the roasting process, the binder is pyrolyzed into reduced carbon in a high-temperature oxygen-deficient environment, and the lead oxide in the manganese slag can be reduced to lead, which is then evaporated into gas at high temperature and condensed after collection, and the lead vapor in the gas is cooled into solid lead to achieve lead recovery, while the iron in the manganese slag is also reduced to iron element, which can achieve the simultaneous recovery of manganese and lead in one step, and at the same time enhance the magnetism of the catalyst, which is convenient for magnetic recovery of the catalyst after use. In this reaction, the carbon in the particles is oxidized into carbon dioxide to overflow and produce an internal pore structure, which preferably increases the porosity of the catalyst and improves the catalytic efficiency.
[0024] In step (5), the drying temperature is 80-120° C., the roasting temperature is 900-1200° C., and the roasting time is 1-2 h.
[0025] Preferably, the calcination is first performed at a low temperature of 400-600° C. for 20-40 min to facilitate the removal of bound water.
[0026] The protective gas used in the calcination in step (5) is not limited to inert gases such as nitrogen and argon.
[0027] The second aspect of the present invention provides an ozone catalytic oxidation catalyst obtained according to the catalyst preparation method provided in the first aspect.
[0028] The second aspect of the present invention provides a method for treating wastewater with an ozone oxidation catalyst, comprising: adding the catalyst prepared as described above to organic wastewater, degrading pollutants under ozone catalytic oxidation conditions, and verifying the catalytic effect and metal ion leaching rate.
[0029] The dosage of the catalyst for treating organic wastewater is 2-10 g / L.
[0030] The COD concentration of the organic wastewater is 1000-4000 mg / L.
[0031] The reaction conditions for degrading pollutants are ozone catalytic oxidation pH=10-13 and temperature of 20-30° C.; the pollutants include di(2-ethylhexyl) phosphate.
[0032] Preferably, the prepared catalyst is added to organic wastewater and soaked in the organic wastewater for 8-12 hours to accelerate the loading of organic molecules in the wastewater.
[0033] After the wastewater treatment is completed, solid-liquid separation is carried out to obtain treated organic wastewater and treatment residue. The treated organic wastewater can be directly discharged or returned for recycling. The treatment residue can continue to be used as a catalyst cycle and can be recovered by magnetic separation after deactivation.
[0034] The beneficial effects of the present invention are:
[0035] Compared with the existing method of removing a small amount of iron from manganese slag, the present invention adopts the opposite process to increase the iron content to enhance the synergistic catalytic effect of iron and manganese to prepare an ozone catalyst, thereby reducing the difficulty of impurity removal and making easy recovery by utilizing magnetism, thereby realizing the rational utilization of manganese resources.
[0036] The present invention adopts pyrolysis reduction of a binder. Compared with the existing reduction method for recovering lead, the present invention has low material cost, low difficulty and safe operation. While effectively recovering the lead in the anode slag, the granulation and magnetization of the anode slag for preparing the catalyst are realized, which not only optimizes and improves the catalyst efficiency, but also shortens the process for subsequent magnetic separation recovery and reduces the cost of manganese slag treatment, thus achieving multiple goals at one stroke.
[0037] The ozone catalyst of the present invention has a good single degradation effect on di(2-ethylhexyl) phosphate wastewater, and the COD removal rate of the wastewater ozone catalytic oxidation reaches 83%, which effectively alleviates the pressure of large-scale organic wastewater treatment in the new energy industry. BRIEF DESCRIPTION OF THE DRAWINGS
[0038] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the drawings required for use in the embodiments are briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present invention and therefore should not be regarded as limiting the scope. For ordinary technicians in this field, other related drawings can be obtained based on these drawings without creative work.
[0039] Figure 1 is a process flow chart of an embodiment of the present invention;
[0040] Figure 2 The photographs of the mixing process of iron-supplemented anode slag and starch in step (4) of Example 1 of the present invention (left: photograph after mixing, right: photograph of evenly stirred);
[0041] Figure 3 These are photos of the magnetic attraction of the catalyst after granulation in step (4) and calcination in step (5) of Example 1 of the present invention (left: granulation; right: magnetic attraction). DETAILED DESCRIPTION
[0042] In order to make the purpose, technical solutions and advantages of the embodiments of the present invention clearer, the technical solutions in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Generally, the components of the embodiments of the present invention described and shown in the drawings here can be arranged and designed in various different configurations.
[0043] Example 1
[0044] (1) The electrolytic anode slag was cleaned with water and mechanically activated, and then the anode slag was dried at 105° C. for 18 h to obtain 50 g of pretreated anode slag;
[0045] (2) 50 g of the pretreated anode slag (the Mn content in the manganese slag was 588.520 g / kg) was fully mixed and stirred with a 20 wt% ferrous sulfate solution (83.16 g), wherein the Fe:Mn molar ratio was 1:5, and the pH was adjusted to 9.46 with a 5 wt% sodium hydroxide solution, filtered, dried, and ground to obtain an iron-supplemented anode slag;
[0046] (3) Add 100 g of starch into 340 g of deionized water, stir and heat to 78° C. to obtain a uniform paste solution;
[0047] (4) adding the iron-supplemented anode slag to the starch paste solution, stirring evenly, and granulating the powdered anode slag using the viscosity of the solution to obtain a prefabricated catalyst;
[0048] (5) The prefabricated catalyst was dried at 105° C. and placed in a muffle furnace for calcination at 500° C. for 30 min to remove bound water, and then calcined at 1050° C. for 1 h under nitrogen protection to prepare the catalyst, and the gas in the reaction was collected.
[0049] Example 2
[0050] The catalyst preparation method of this embodiment is the same as that of embodiment 1, except that in step (2), 20 wt % ferrous chloride solution is used to replace ferrous sulfate solution, and the added amount is 33.89 g, so that the Fe:Mn molar ratio is 1:10.
[0051] Example 3
[0052] The catalyst preparation method of this embodiment is the same as that of embodiment 1, except that the pH value in step (2) is 9, and the calcination condition in step (5) is 1050° C. for 2 h.
[0053] Example 4
[0054] The catalyst preparation method of this embodiment is the same as that of embodiment 1, with the only difference being that in step (5), the prefabricated catalyst is dried at 105°C and then placed in a muffle furnace and directly calcined at 1050°C for 1 hour, and high-temperature calcination treatment is performed under nitrogen protection to prepare the catalyst, and the gas in the reaction is collected.
[0055] Example 5
[0056] The catalyst preparation method of this embodiment is the same as that of Example 1, except that, in step (2), 50 g of anode slag is thoroughly mixed with 20 wt% ferrous sulfate solution (74.56 g) and 20 wt% ferrous lactate solution (12.76 g) to uniformly stir, wherein the molar ratio of Fe:Mn is 1:5, and the molar ratio of ferrous lactate to ferrous sulfate is 0.1:1; the pH is adjusted to 9.46 with 5 wt% sodium hydroxide solution, filtered, dried, and ground to obtain iron-supplemented anode slag.
[0057] Example 6
[0058] The catalyst preparation method of this embodiment is the same as that of Example 2, except that, in step (2), 50 g of anode slag is thoroughly mixed with 20 wt% ferrous chloride solution (30.5 g) and 10 wt% ferrous lactate solution (12.53 g) to uniformly stir, wherein the Fe:Mn molar ratio is 1:10, and the molar ratio of ferrous lactate to ferrous chloride is 0.1:1; the pH is adjusted to 9.46 with 5 wt% sodium hydroxide solution, filtered, dried, and ground to obtain iron-supplemented anode slag.
[0059] Comparative Example 1
[0060] The catalyst preparation method of this comparative example is the same as that of Example 1, except that step (2) is omitted, the anode slag is not supplemented with iron, and starch solution is directly added for granulation.
[0061] Comparative Example 2
[0062] The catalyst preparation method of this comparative example is the same as that of Example 1, except that steps (3)-(4) are omitted, the catalyst is directly fired after the anode slag is supplemented with iron, and starch is not added for granulation.
[0063] Catalytic performance test:
[0064] The catalysts prepared in the above examples and comparative examples were used to treat organic wastewater containing di(2-ethylhexyl) phosphate, and the specific operation was as follows:
[0065] 2 g of the prepared catalyst was weighed and put into organic wastewater with a pH of 11.5 (actual production wastewater of a new energy vehicle battery company for producing nickel-cobalt-manganese ternary precursor powder, COD = 2269.53 mg / L) for ozone catalytic oxidation experiment. The ozone generator flow rate was set to 1 L / min, the ozone concentration was 75%, and the reaction time was 2 h. The COD concentration in the wastewater was determined by the potassium dichromate method HJ828-2017 to verify the catalytic effect of the catalyst, as shown in Table 1.
[0066] Table 1 Comparison of experimental effects of ozone catalytic oxidation examples and comparative examples
[0067]
[0068] Note: ND means not detectable.
[0069] Table 1 shows that the catalyst of embodiment 1-6 of the present invention treats organic wastewater, and can realize COD removal rate higher than 83%. This is also because the present invention adopts iron supplementation to enhance the catalytic efficiency of active components while optimizing the pore structure of the catalyst, greatly improving the effect of catalyst in removing organic pollutants, while Mn and Fe concentrations in the wastewater are relatively low, and are all within a certain range (Mn and Fe concentrations are both lower than 0.1mg / l), which can explain that the precipitation of Fe and Mn elements after treatment reaction is relatively stable, which also illustrates that the catalyst has certain stability. In addition, the Pb concentration in the wastewater is almost undetectable, and it is also because the present invention adopts starch pyrolysis reduction to reduce the Pb in the manganese slag into solid lead, so it is undetectable. The ozone catalyst of the present invention can directly adopt magnetic recovery, realizes the rational utilization of manganese slag, and is suitable for industrial promotion.
[0070] Compared with Example 1, in Example 5, due to the addition of organic ferrous salt, the pore structure and porosity of the catalyst are further optimized, thereby improving the efficiency of the catalyst in degrading COD, which can be as high as 87.1%, and has excellent treatment efficiency for the treatment of organic wastewater containing di(2-ethylhexyl) phosphate in the new energy industry. Similarly, the catalyst wastewater treatment effect of Example 6 is also improved.
[0071] Comparative Example 1 did not carry out iron supplementation, and the Mn-Fe synergistic effect could not be achieved, so the catalyst efficiency decreased; Comparative Example 2 did not use starch granulation, and the catalyst pore structure could not be fully improved, so the catalyst COD removal rate was also reduced, and it was not conducive to the recovery of the catalyst.
[0072] The above-described embodiments are only specific implementations of the present invention, which are used to illustrate the technical solutions of the present invention, rather than to limit them. The protection scope of the present invention is not limited thereto. Although the present invention is described in detail with reference to the above-described embodiments, ordinary technicians in the field should understand that any technician familiar with the technical field can still modify the technical solutions recorded in the above-described embodiments within the technical scope disclosed by the present invention, or can easily think of changes, or make equivalent replacements for some of the technical features therein; and these modifications, changes or replacements do not make the essence of the corresponding technical solutions deviate from the spirit and scope of the technical solutions of the embodiments of the present invention, and should be included in the protection scope of the present invention. Therefore, the protection scope of the present invention shall be based on the protection scope of the claims.
Claims
1. A method for preparing an ozone oxidation catalyst based on electrolytic anode manganese slag, characterized in that: The following steps are involved: (1) Cleaning, mechanically activating and drying the electrolytic anode slag to obtain pretreated anode slag; (2) mixing the pretreated anode slag obtained in step (1) with an iron salt solution, adjusting the pH value, filtering, drying and grinding to obtain an iron-supplemented anode slag; the iron salt solution is a ferrous salt solution; based on the molar amount of Mn in the anode slag, the molar ratio of Fe:Mn is 1:(1-10); (3) Add starch to deionized water, stir and heat to 70-85°C to obtain a paste-like binder solution; (4) adding the iron-supplemented anode slag obtained in step (2) to the binder solution in step (3), stirring and granulating to obtain a prefabricated catalyst; (5) drying, calcining and cooling the prefabricated catalyst to obtain the ozone oxidation catalyst; The calcination is firstly carried out at a low temperature of 400-600° C. for 20-40 minutes, and then at 900-1200° C. for 1-2 hours.
2. The method according to claim 1, characterized in that The mechanical activation in step (1) is to grind the electrolytic anode slag to a particle size of 10-75um; the drying temperature is 80°C-150°C.
3. The method according to claim 1, characterized in that The pH value in step (2) is in the range of 8.5-9.5, and the drying temperature is 80°C-150°C.
4. The method according to claim 1, characterized in that The mass ratio of the binder in step (3) to the iron-replenishing anode slag obtained in step (2) is (1-3):
1.
5. The method according to claim 1, characterized in that In step (5), the drying temperature is 80-120°C, the roasting temperature is 900-1200°C, and the roasting time is 1-2h.
6. The method according to claim 1, characterized in that The ferrous salt is a mixed solution of an organic ferrous salt and an inorganic ferrous salt, and the organic ferrous salt solution is selected from ferrous lactate or ferrous gluconate solution; wherein the molar ratio of the organic ferrous salt to the inorganic ferrous salt is (1-2):
10.
7. An ozone oxidation catalyst prepared according to the method according to any one of claims 1 to 6.
8. The method for treating organic wastewater using the catalyst according to claim 7, characterized in that: The pollutants in the organic wastewater include di(2-ethylhexyl) phosphate, the amount of the catalyst used to treat the organic wastewater is 2-10 g / L, the COD concentration of the organic wastewater is 1000-4000 mg / L, and the reaction conditions for treating the organic wastewater are pH=10-13 and temperature of 20-30°C.
Citation Information
Patent Citations
Method for recovering manganese and lead from electrolytic manganese anode slag
CN112760487A
Electrolytic manganese metal anode slag recovery treatment method
CN115261631A
Application of modified manganese sand to catalysis of degradation of organic wastewater by hydrogen peroxide
CN109759079A
Method for preparing battery-grade manganese dioxide by utilizing anode slag
CN112645387A
